Riscos dos produtos e serviços de saúde: conceitos e vivências nos Centros de Atenção Psicossocial - Sales Neto, Manoel Ribeiro de (2022)
It is argued that potential risk, understood as the possibility of an event occurring, constitutes the most appropriate risk concept for Health Surveillance. This thesis elucidates the risks of health products and services defined by the literature concerning Sanitary Surveillance and experienced by users and workers in the context of Psychosocial Care Centers in a Brazilian capital. To achieve this purpose, two stages were developed. The integrative review of risk concepts was carried out in a bank of legislation and in four databases. A theory and a typology underpinned the categorization. 14 normative acts and 20 articles were selected. The empirical stage involved interviews with users and workers at the Psychosocial Care Centers and Health Surveillance. The limitations of some definitions were pointed out, such as the difficulty of calculating the probability of events. There are divergences between articles and normative acts regarding the terminology adopted to refer to risk. The definitions are composed of different terms, which are not always capable of being differentiated. Only one article investigates the meanings that professionals attribute to risk. Potential risk, an expression that has different definitions in Brazil and Russia, is mainly used to standardize risk assessment. Risk is conceptualized qualitatively by workers and users, as recommended by the literature. Risks are experienced from the relationship that knowledge builds between objects at risk and the object at risk of health. Users are considered as objects of risk to the health of workers. It was found that risk management is cosmetic, in the sense that attempts to eliminate or reduce risk do not achieve these purposes. Furthermore, normative risk objects are not recognized by people with mental disorders or valued by CAPS workers. A convergent effort is needed to intensify the use of the Brazilian theoretical definition attributed to potential risk and to minimize the variety of terms used in risk definitions. Health Surveillance needs to be recognized as an entity that can contribute to effective risk management. It also proposes the adoption of measures that deconstruct the association between dangerousness and mental disorders.